Analisis Kurikulum Pendidikan Agam Islam pada kelas VIII (Delapan) MTS N 1 Kota Bengkulu - Agus Delianto; Al Fauzan Amin; Rohimin Rohimin; Ahmad Suradi; Nefi Aprianti (Departement of Mathematics Education, 2024)
The curriculum currently implemented in schools at both primary and secondary levels is a transitional curriculum, namely the independent learning curriculum. The independent curriculum has its own special features, one of which is an effort to form national character, in the form of the Rahmatan Lil Alamin Student Profile which is expected to provide opportunities or chances in forming madrasas and teaching staff in developing an independent curriculum through the Rahmatan Lil Alamin Student Profile Curriculum as an effort to achieve the goal which has been determined in accordance with the existing curriculum, where this curriculum has material content that is more humanistic in strengthening tolerance and moderation. The research uses qualitative research techniques with a descriptive approach. This research was conducted at MTS Negeri 01 Bengkulu City. The Islamic religious education curriculum based on character education is an important object to continue to develop in educational institutions. Character education ultimately has a direct impact in shaping the character of students so that they comply with the commandments of the Islamic religion and become guidelines for actions and behavior in life. P5-PPRA which is implemented at MTSN 1 Bengkulu City plays a very important role, of course in relation to subjects, training and extracurricular activities. The strategies for implementing Character Education in the independent curriculum with P5-PPRA at MTS N 1 Bengkulu City are: identification of Islamic religious values, development of teaching materials, teacher example, active learning and participation, and character training through extracurricular activities